2013
DOI: 10.2478/v10136-012-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of β-catenin on proliferation of hair follicle stem cells involves PI3K/Akt pathway

Abstract: β-catenin signaling is required for hair follicle development and regeneration which are involved in the resuscitation of hair follicle stem cells (HFSCs). To further characterize the role of β-catenin in the regulation of proliferation of HFSCs, the β-catenin expression was measured in the defined stages of hair follicle cycle and the proliferative potency was determined by using an in vitro cell growth assay. Our results showed that activation of β-catenin correlated with HFSCs proliferation, which appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Previous studies have demonstrated that Akt regulates expression of β-catenin and the β-catenin signaling also participates in the regulation of Akt expression (18)(19)(20). Furthermore, it appears β-catenin regulates cell proliferation via activation of the PI3K/Akt pathway (21). In the present study, overexpression of β-catenin in the late passage of bmMSCs also enhanced Akt1 expression.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have demonstrated that Akt regulates expression of β-catenin and the β-catenin signaling also participates in the regulation of Akt expression (18)(19)(20). Furthermore, it appears β-catenin regulates cell proliferation via activation of the PI3K/Akt pathway (21). In the present study, overexpression of β-catenin in the late passage of bmMSCs also enhanced Akt1 expression.…”
Section: Discussionsupporting
confidence: 71%
“…It is well-known that activating the Wnt/β-catenin signaling pathway by inhibiting GSK-3β induces β-catenin phosphorylation and degradation, promoting DPC proliferation [ 15 , 20 , 23 , 30 ]. Therefore, we examined the protein levels of β-catenin, phosphorylated GSK-3β (p-GSK-3β [SER9]), p-AKT, and cyclin D1, which are all known to mediate cell proliferation, by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Androgenetic alopecia is characterized by small-sized hair follicles and a shortening anagen phase. A recent study showed that a hair follicle went into a new anagen from the last telogen when the quiescent stem cells were stimulated to promote proliferation in response to signals from the DP [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several signal pathways and molecules were implicated in regulating the differentiation of hair follicle stem cells into hair follicle lineages, such as Wnt/β-catenin [6], Lef1 [7], Lhx2 [8], TCF3 [9,10], Wnt10b [11], and c-myc [12]. Additionally, non-coding RNAs might play roles in regulating the differentiation of hair follicle stem cells into hair follicle lineages, like miR-22 [13], and LncRNA-PlncRNA 1 [6].…”
Section: Introductionmentioning
confidence: 99%